Favourable effects of grape seed extract on intestinal epithelial differentiation and barrier function in IL10-deficient mice. Issue 1 (20th May 2015) - Yang, Guan; Xue, Yansong; Zhang, Hanying; Du, Min; Zhu, Mei-Jun
Abstract : The impairment in the rate of cell proliferation and differentiation leads to a negative consequence on the renewal of the intestinal epithelium, which is the aetiological factor of a number of digestive diseases. Grape seed extract (GSE), a rich source of proanthocyanidins, is known for its beneficial health effects. The present study evaluated the beneficial effects of GSE on colonic cell differentiation and barrier function in IL10-deficient mice. Female mice aged 6 weeks were randomised into two groups and given drinking-water containing 0 or 0·1 % GSE (w/v) for 12 weeks. GSE supplementation decreased serum TNF-α level and intestinal permeability, and increased the colonic goblet cell density that was associated with increased mRNA expression of mucin ( Muc )-2. Immunohistochemical analyses showed lower accumulation of β-catenin in the crypts of colon tissues of the GSE-supplemented mice, which was associated with a decreased mRNA expression of two downstream effectors of Wingless and Int (Wnt)/catenin signalling, myelocytomatosis oncogene protein ( Myc ) and cyclin D1 ( Ccnd1 ). Consistently, GSE supplementation decreased the number of colonic proliferating cell nuclear antigen-positive cells, a well-known cell proliferation marker, and a weakened extracellular signal-regulated kinases 1 and 2 (ERK1/2) signalling. In summary, these data indicate that supplementation of 0·1 % GSE for 12 weeks improved gut barrier function and colonic cell differentiation in the IL10-deficient mice probably via inhibiting Wnt/β-catenin pathway.